2008
DOI: 10.1002/jmri.21536
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of pacemaker lead heating induced by magnetic resonance imaging: Role of implant geometry

Abstract: Purpose:To evaluate the effect of the geometry of implantable pacemakers (PMs) on lead heating induced by magnetic resonance imaging (MRI). Materials and Methods:In vitro experiments were conducted with two different setups, using fluoroptic probes to measure the temperature increase. The first experiment consisted of a rectangular box filled with a gelled saline and a pacemaker with its leads. This box was exposed in an MRI birdcage coil to a sinusoidal 64-MHz field with a calibrated whole-body specific absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 21 publications
3
39
1
Order By: Relevance
“…The WB-SAR of 1 W/ kg adopted during the heating tests is a typical value of clinical RF sequences for the MRI scanning, considering that the threshold of 2 W/kg is the maximum value allowed by the normal operating mode defined in IEC 60601-2-33. Given the 1 W/kg exposure, the temperature increases and SAR values obtained are consistent with the findings of previous studies (17,18,23).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The WB-SAR of 1 W/ kg adopted during the heating tests is a typical value of clinical RF sequences for the MRI scanning, considering that the threshold of 2 W/kg is the maximum value allowed by the normal operating mode defined in IEC 60601-2-33. Given the 1 W/kg exposure, the temperature increases and SAR values obtained are consistent with the findings of previous studies (17,18,23).…”
Section: Discussionsupporting
confidence: 90%
“…The system is installed at the Department of Technology and Health of the Italian National Institute of Health and has been specially designed to provide a controlled exposure for MRI safety testing with regards to the RF field. Systems with the same features have been widely used in previous published studies (17,(22)(23)(24). It has also been demonstrated that, given the same implant configuration and the same WB-SAR delivered to the phantom, the induced heating inside the isolated birdcage coil is comparable with the one obtained in an actual MRI system using clinical MRI sequences (23).…”
Section: Exposure Systemmentioning
confidence: 86%
See 2 more Smart Citations
“…Metallic devices and leads can act as an antenna thus amplifying local radiofrequency energy deposition. [8][9][10] Fractured leads or lead loop configurations may increase the potential for heating. Epicardial leads that are not cooled by blood flow 11 and abandoned leads may also be prone to increased heating.…”
Section: Physics Of Mri Related To Devicesmentioning
confidence: 99%